The Transcendental Basis of Critical Reflection - Pilotta, Joe (Sociologija. Mintis ir veiksmas, 2002)
It is a premise of this paper that phenomenological social science is not nor aspires to be phenomenological philosophy. Phenomenological social science has more than sufficient tasks before it to dissuade it from extending itself into philosophical domains of inquiry. Furthermore, it is our assumption, or rather, the goal of demonstration that phenomenological social scientific reflection does not need to be paradoxical; but that the way out of the paradox presupposes the validity and the effectiveness of the transcendental orientation. The following analysis is abbreviated; it merely sketches some of the main points for clarification. The paper has two sections. The first attempts to demarcate the domain of social scientific reflection and provides a listing of significant theoretical and semantic considerations pertinent to the lifeworld grounding of social scientific inquiry. The section draws attention to the systematic function of transcendental reflection in phenomenological social science.